Boundary Value Problems for q-Difference Inclusions - Bashir Ahmad; Sotiris K. Ntouyas (Abstract and Applied Analysis)
We investigate the existence of solutions for a class of second-order q-difference inclusions with nonseparated boundary conditions. By using suitable fixed-point theorems, we study the cases when the right-hand side of the inclusions has convex as well as nonconvex values.